2022
DOI: 10.1523/jneurosci.0658-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Target Detection at Local and Global Timescales Reveals a Hierarchy of Supramodal Dynamics in the Human Cortex

Abstract: To ensure survival in a dynamic environment, the human neocortex monitors input streams from different sensory organs for important sensory events. Which principles govern whether different senses share common or modality-specific brain networks for sensory target detection? We examined whether complex targets evoke sustained supramodal activity while simple targets rely on modality-specific networks with short-lived supramodal contributions. In a series of hierarchical multisensory target detection studies (n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…We showed that early and late MMRs in our EEG data were best explained by a Bayesian observer tracking stimulus transition probabilities and that more central and later responses around the P3 appeared to specifically track stimulus transitions across multiple modalities. In recent MMR research, the local–global paradigm has revealed that the early MMN and the later P3 reflect two hierarchical stages of mismatch processing signaling regularity violation on increasing levels of sequence complexity (Bekinschtein et al, 2009 ; Chennu et al, 2013 ; Chennu et al, 2016 ; Dehaene et al, 2015 ; Dürschmid et al, 2016 ; El Karoui et al, 2015 ; King et al, 2014 ; Niedernhuber et al, 2022 ; Shirazibeheshti et al, 2018 ; Wacongne et al, 2011 ): While the MMN is primarily sensitive to local regularities, such as basic stimulus repetition, the P3 is additionally sensitive to global regularities such as a repeating pattern over an extended period of time. In addition to global sequence monitoring with respect to temporal regularities, the P3 appears to additionally be sensitive to global sequence regularities in terms of the multi‐modal stimulus configuration (Grundei et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that early and late MMRs in our EEG data were best explained by a Bayesian observer tracking stimulus transition probabilities and that more central and later responses around the P3 appeared to specifically track stimulus transitions across multiple modalities. In recent MMR research, the local–global paradigm has revealed that the early MMN and the later P3 reflect two hierarchical stages of mismatch processing signaling regularity violation on increasing levels of sequence complexity (Bekinschtein et al, 2009 ; Chennu et al, 2013 ; Chennu et al, 2016 ; Dehaene et al, 2015 ; Dürschmid et al, 2016 ; El Karoui et al, 2015 ; King et al, 2014 ; Niedernhuber et al, 2022 ; Shirazibeheshti et al, 2018 ; Wacongne et al, 2011 ): While the MMN is primarily sensitive to local regularities, such as basic stimulus repetition, the P3 is additionally sensitive to global regularities such as a repeating pattern over an extended period of time. In addition to global sequence monitoring with respect to temporal regularities, the P3 appears to additionally be sensitive to global sequence regularities in terms of the multi‐modal stimulus configuration (Grundei et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been proposed that the deviance detection system of MMN and P3 differentially responds to expectation violation to sequence regularities on different levels of complexity. Studies employing the “local–global” paradigm (Bekinschtein et al, 2009 ) in which stimulus sequences are defined by local regularities (e.g., the tendency of a stimulus to repeat) and additional global regularities (e.g., every fifth stimulus in a repeated sequence is a deviant) show that the MMN is only elicited by the local regularity violations whereas the later P3 is additionally sensitive to violations of the global deviant regularity (Bekinschtein et al, 2009 ; Chennu et al, 2013 ; Chennu et al, 2016 ; Dürschmid et al, 2016 ; El Karoui et al, 2015 ; King et al, 2014 ; Niedernhuber et al, 2022 ; Shirazibeheshti et al, 2018 ; Wacongne et al, 2011 ). Strikingly, this dichotomy for MMRs was recently shown to hold for the auditory, somatosensory and visual modality alike (Niedernhuber et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different brain regions are purported to extract regularity information over different temporal intervals such that shorter timescale information that can be gleaned by sensory areas is modulated by longer timescale information supported by more rostral areas, such as the prefrontal cortex 136–138 . Patterns that are only evident over longer timescales can therefore theoretically be used to weight the dependence of MMN on higher areas of the cortical network 139–142 . Finally, theoretical perspectives on the varied reasons for different MMN amplitudes have also progressed.…”
Section: Do Methods Matter To What We Learn About Mmn In Schizophrenia?mentioning
confidence: 99%
“… 136 , 137 , 138 Patterns that are only evident over longer timescales can therefore theoretically be used to weight the dependence of MMN on higher areas of the cortical network. 139 , 140 , 141 , 142 Finally, theoretical perspectives on the varied reasons for different MMN amplitudes have also progressed. What was once considered probabilistic inference based on sensory memory 5 has been augmented by evidence of statistical learning of transitional probability 143 and even speculation that the system is engaged in hierarchical inference.…”
Section: Do Methods Matter To What We Learn About Mmn In Schizophrenia?mentioning
confidence: 99%